2005
DOI: 10.1007/s00442-005-0277-z
|View full text |Cite
|
Sign up to set email alerts
|

Turnover rates of nitrogen stable isotopes in the salt marsh mummichog, Fundulus heteroclitus, following a laboratory diet switch

Abstract: Nitrogen stable isotopes are frequently used in ecological studies to estimate trophic position and determine movement patterns. Knowledge of tissuespecific turnover and nitrogen discrimination for study organisms is important for accurate interpretation of isotopic data. We measured δ 15 N turnover in liver and muscle tissue in juvenile mummichogs, Fundulus heteroclitus, following a laboratory diet switch. Liver tissue turned over significantly faster than muscle tissue suggesting the potential for a multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
70
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 33 publications
6
70
2
2
Order By: Relevance
“…Such results indicate that metabolism is not always negligible in the isotope turnover of fish tissue (Herzka & Holt 2000, Marcogliese 2001, Harvey et al 2002. Similar results were also reported for whitefish Coregonus lavaretus (Perga & Gerdeaux 2005), juvenile mummichogs Fundulus heteroclitus (Logan et al 2006), and juvenile sand goby Pomatoschistus minutus (Guelinckx et al 2007).…”
Section: Discussionsupporting
confidence: 78%
“…Such results indicate that metabolism is not always negligible in the isotope turnover of fish tissue (Herzka & Holt 2000, Marcogliese 2001, Harvey et al 2002. Similar results were also reported for whitefish Coregonus lavaretus (Perga & Gerdeaux 2005), juvenile mummichogs Fundulus heteroclitus (Logan et al 2006), and juvenile sand goby Pomatoschistus minutus (Guelinckx et al 2007).…”
Section: Discussionsupporting
confidence: 78%
“…This also raises some caution as to the applicability of these predictions to older life-stages, where individuals are likely to be slower growing and sexually mature (Hesslein et al, 1993;Herzka & Holt, 2000;Perga & Gerdeaux, 2005). Where experimental studies have been completed on larger or older fishes, and those with lower specific growth rates, the results suggest that metabolic replacement contributes a major proportion of total turnover, in some cases accounting for 80% of isotopic change in dorsal muscle (Suzuki et al, 2005;Logan et al, 2006;Tarboush et al, 2006). Heady and Moore (2013) revealed that catabolism contributed more to 15 N turnover in tissues with faster turnover rates, contributing 68% for fin compared to 0.7% for scales.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than relying on data collected in the wild, an alternative approach is the use of experimental diet-switch studies completed in controlled conditions (Heady & Moore, 2013;Xia et al, 2013a, b;Busst & Britton, 2016). In these studies, diet tends to be fixed so that the food items have relatively consistent stable isotope values that should provide more reliable turnover estimates in the tissues (Logan et al, 2006). These approaches should also provide enhanced understandings of the mechanisms involved in isotopic replacement (Buchheister & Latour, 2010;Heady & Moore, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Compound specific isotope analyses (e.g. Popp et al 2007, Olson et al 2010) and/or the use of a rapid turnover tissue such as liver or blood that reflects short-term, local feeding (MacNeil et al 2006, Logan et al 2006) could help resolve this question, but this was not possible due to logistic and ethical constraints.…”
mentioning
confidence: 99%